Temperature-resistant and salt-resistant copolymer with filtration loss reducing, viscosity increasing and lubricating properties as well as preparation method and application of temperature-resistant and salt-resistant copolymer
By using natural polymer materials to graft the dendritic copolymers in the drilling fluid, the problems of many types of drilling fluid treatment agents and high addition amounts are solved, excellent anti-glow lubrication performance at high temperatures, and the drilling fluid formula is simplified And reduces the risk of environmental pollution.
Patent Information
- Application Number
- CN202310766686.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-27
AI Technical Summary
The existing drilling fluid treatment agent has many types and high amounts of addition, which is difficult to meet the high requirements for temperature, rheology and lubrication performance of deep formation drilling construction. At the same time, there are problems such as environmental pollution risk and complex formulation.
Using natural polymer materials (such as corn starch and sweet potato starch) as the central core, dendritic copolymers are formed by grafting organic acid anhydrides, vinyl-containing sulfonates, anionic monomers and crosslinked monomers to prepare a dendritic copolymer with reduced filtration loss , anti-temperature and salt copolymer with viscosity enhancement and lubricating properties.
It achieves excellent temperature and salt resistance at high temperatures, significantly reduces the amount of drilling fluid treatment agent, simplifies the drilling fluid system formulation, reduces construction difficulty and cost, and reduces the risk of environmental pollution.
Smart Images

Figure BDA0004306486870000071 
Figure BDA0004306486870000072 
Figure BDA0004306486870000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield chemistry, and more specifically to a temperature-resistant and salt-resistant copolymer with fluid loss reduction, viscosity increase and lubrication properties, and a preparation method and application thereof. Background Art
[0002] In oil and gas exploration and development, drilling fluid, as the blood of drilling engineering, undertakes the functions of balancing formation pressure, stabilizing well wall, carrying cuttings, cooling and lubricating, and transmitting water power. As the exploration and development of conventional oil and gas resources gradually expand to deep formations, in order to meet the performance requirements of drilling fluid temperature resistance, filtration loss control, plugging and anti-collapse, lubrication, etc., polysulfone drilling fluid system is usually used in China. This system has the characteristics of good temperature resistance and salt resistance, which has promoted the progress of drilling technology in my country. However, the shortcomings of this system are also obvious, mainly including two aspects: First, the formula is complex and there are many types of treatment agents, which leads to cumbersome treatment and maintenance procedures. Taking a well in Tahe work area as an example, the formula of the polysulfone drilling fluid system contains 11 treatment agents, with an addition of more than 15%, of which only the filtration loss reducer has 6 treatment agents such as polymers and resins, with an addition of more than 10%. Second, it is highly toxic, has a high risk of environmental pollution, and is difficult to post-process. The core treatment agents in the system, such as sulfonated asphalt and SMP, are moderately toxic / slightly toxic, with low biodegradation index, and do not meet environmental protection requirements. 50 <1000mg / L, BOD 5 / COD Cr <0.1, difficult to biodegrade and harmlessly dispose of.
[0003] In order to overcome the above-mentioned problems of drilling fluid treatment agents, since the 1990s, a small number of multifunctional products with multiple application effects have been formed by expanding other functions with filtration reduction as the core function. For example, filtration reduction agents have both inhibition and flow control functions, and the drilling fluid system has begun to be gradually simplified.
[0004] Multifunctional drilling fluid treatment agent products are generally centered on fluid loss reduction function. By expanding other functions, fluid loss reducers can also have the effects of reducing viscosity / increasing viscosity and stabilizing the wellbore. Domestic multifunctional treatment agent products are mostly concentrated in "one agent for two purposes". On the basis of fluid loss reduction function, other components with functional groups such as amine and ester groups are introduced to improve the inhibition and lubrication performance. Existing multifunctional drilling fluid treatment agent products actually achieve the effects of fluid loss reduction, wellbore stabilization, flow pattern adjustment, etc. through multi-component compounding. They are actually "one bag" rather than "one dose". There is a lack of "one dose" drilling fluid treatment agent products that can efficiently achieve multiple functions and effects.
[0005] The conventional polysulfone drilling fluid with a temperature resistance of 180°C currently used can meet the temperature resistance requirements of most drilling construction. The filtrate reducers in the polysulfone drilling fluid system are mainly sulfonated materials and polymers, with many types and high addition amounts. In addition, in the face of the requirements of deep formation drilling construction, in order to smoothly carry the underground drill cuttings out of the wellhead and speed up the drilling speed, the drilling fluid is required to resist temperature, and higher requirements are also placed on the rheological properties and lubrication properties of the drilling fluid at high temperatures. Therefore, it is urgent to develop a "one-dose" drilling fluid treatment agent product with excellent temperature resistance, good rheological properties and lubrication properties at high temperatures, and a small addition amount. Summary of the invention
[0006] The object of the present invention is to provide a temperature-resistant and salt-resistant copolymer with filtration loss reduction, viscosity increase and lubrication performance and a preparation method thereof, so as to solve the technical problem of multiple types and high addition amounts of drilling fluid treatment agents in the prior art.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] In the first aspect, the present invention provides a method for preparing a temperature-resistant and salt-resistant copolymer with the properties of reducing filtration loss, increasing viscosity and lubricating, comprising: reacting raw material components including natural polymer materials, organic acid anhydrides, vinyl-containing sulfonates, anionic monomers, cross-linking monomers and initiators in a solvent to obtain the temperature-resistant and salt-resistant copolymer with the properties of reducing filtration loss, increasing viscosity and lubricating.
[0009] According to some embodiments of the present invention, the natural polymer material is a starch-based natural polymer material.
[0010] According to some embodiments of the present invention, the natural polymer material includes at least one of corn starch and sweet potato starch.
[0011] According to some embodiments of the present invention, the organic acid anhydride includes at least one selected from phthalic anhydride and maleic anhydride.
[0012] According to some embodiments of the present invention, the vinyl-containing sulfonate comprises at least one of sodium styrene sulfonate and sodium allyl sulfonate.
[0013] According to some embodiments of the present invention, the anionic monomer includes 2-acrylamide-2-methylpropanesulfonic acid (AMPS).
[0014] According to some embodiments of the present invention, the cross-linking monomer includes at least one of acrylamide and N-methylol acrylamide.
[0015] According to some embodiments of the invention, the initiator comprises at least one of ammonium persulfate and potassium persulfate.
[0016] According to some embodiments of the invention, the solvent comprises water.
[0017] In the present invention, a dendritic copolymer is formed by using a starch-based natural polymer material as a "central core" and grafting an organic anhydride, a vinyl-containing sulfonate, an anionic monomer and a crosslinking monomer thereon. The copolymer has excellent temperature and salt resistance, and also has good fluid loss reduction, viscosity increase and lubrication properties.
[0018] According to some embodiments of the present invention, the amounts of the components include:
[0019] Solvent: 100 parts by weight;
[0020] Natural polymer material: 2-3 parts by weight;
[0021] Organic acid anhydride: 10-40 parts by weight;
[0022] Vinyl-containing sulfonate: 4 to 10 parts by weight;
[0023] Anionic monomer: 20-30 parts by weight;
[0024] Cross-linking monomer: 1 to 6 parts by weight;
[0025] Initiator: 0.5-1 parts by weight.
[0026] According to some embodiments of the present invention, the amounts of the components include:
[0027] Solvent: 100 parts by weight;
[0028] Natural polymer material: 2-3 parts by weight;
[0029] Organic acid anhydride: 20-30 parts by weight;
[0030] Vinyl-containing sulfonate: 5 to 8 parts by weight;
[0031] Anionic monomer: 24-26 parts by weight;
[0032] Cross-linking monomer: 3-4 parts by weight;
[0033] Initiator: 0.5-1 parts by weight.
[0034] According to some embodiments of the present invention, the preparation method comprises:
[0035] The natural polymer material and the solvent are mixed and stirred; then the organic anhydride, the vinyl-containing sulfonate, the anionic monomer and the cross-linking monomer are added in sequence and stirred to dissolve; then the initiator is added and stirred to react at 60-80° C. to obtain the temperature-resistant and salt-resistant copolymer with the properties of reducing filtration loss, increasing viscosity and lubricating.
[0036] According to some embodiments of the present invention, the stirring speed is 300-500 r / min.
[0037] According to some embodiments of the present invention, the stirring reaction time is 2 to 8 minutes.
[0038] According to some embodiments of the present invention, the preparation method further comprises: drying, crushing and sieving the reaction product.
[0039] According to some embodiments of the present invention, the drying temperature is 90 to 110° C., and the drying time is 16 to 30 hours.
[0040] According to some embodiments of the present invention, the mesh size of the sieve is 0.59 mm.
[0041] In a second aspect, the present invention provides a temperature-resistant and salt-resistant copolymer having fluid loss reduction, viscosity increase and lubrication properties, which is prepared by the preparation method described in the first aspect.
[0042] In a third aspect, the present invention provides the use of the temperature-resistant and salt-resistant copolymer with fluid loss reduction, viscosity increase and lubrication properties described in the second aspect in drilling fluid.
[0043] In a fourth aspect, the present invention provides a drilling fluid, comprising the temperature-resistant and salt-resistant copolymer with filtration loss reduction, viscosity increase and lubrication properties as described in the third aspect.
[0044] According to some embodiments of the present invention, the drilling fluid further comprises water, bentonite and sodium chloride.
[0045] According to some embodiments of the present invention, in the drilling fluid, based on 100 parts by weight of water, the amount of bentonite is 3 to 5 parts by weight, the amount of sodium chloride is 20 to 30 parts by weight, and the amount of the temperature- and salt-resistant copolymer with filtration loss reduction, viscosity increase, and lubrication properties described in the third aspect is 2 to 4 parts by weight.
[0046] The beneficial effects of the present invention are at least:
[0047] The temperature-resistant and salt-resistant copolymer with filtration reduction, viscosity increase and lubrication performance provided by the present invention has excellent temperature-resistant and salt-resistant performance, and has good filtration reduction, viscosity increase and lubrication performance. The temperature-resistant and salt-resistant copolymer with filtration reduction, viscosity increase and lubrication performance provided by the present invention is used in a conventional drilling fluid system with a temperature resistance of 180°C, which can significantly reduce the amount of drilling fluid treatment agents such as filtration reducers, viscosity increasers, and lubricants while maintaining comparable performance, greatly simplifying the formula of the high-temperature resistant drilling fluid system, greatly reducing the cost of drilling fluid, and can effectively reduce the construction difficulty and construction work intensity. DETAILED DESCRIPTION
[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.
[0049] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0050] In each embodiment and comparative example of the present invention, the materials used are all industrial products, as follows:
[0051] Corn starch: Zhengzhou Yuhe Food Additive Co., Ltd.
[0052] Sweet potato starch: Zhengzhou Yuhe Food Additive Co., Ltd.
[0053] Phthalic anhydride: Shanghai Guyan Technology Co., Ltd.
[0054] Maleic anhydride: Tianjin Damao Chemical Reagent Factory.
[0055] Sodium styrene sulfonate: Shanghai McLean Biochemical Technology Co., Ltd.
[0056] Sodium allyl sulfonate: Guangdong Wengjiang Chemical Reagent Co., Ltd.
[0057] 2-Acrylamido-2-methylpropanesulfonic acid (AMPS): Shandong Qicai Chemical Co., Ltd.
[0058] Acrylamide: Shandong Zibo Juxin Chemical Co., Ltd.
[0059] N-Hydroxymethyl acrylamide: Shanghai Gaoming Chemical Co., Ltd.
[0060] Potassium persulfate: Jinan Fengle Chemical Co., Ltd.
[0061] Ammonium persulfate: Jinan Fengle Chemical Co., Ltd.
[0062] In the performance tests of the copolymers prepared in the various embodiments and comparative examples of the present invention, the test methods used include:
[0063] (1) Evaluation of fluid loss reduction performance: 12 g of the copolymer prepared in each embodiment or comparative example was added to the base slurry at a high-speed stirrer speed of 11000 r / min and stirred for 20 min. After aging in a roller furnace at 180°C for 16 h, the slurry was taken out and cooled to room temperature. The high-temperature and high-pressure fluid loss was evaluated at 180°C and 3.5 MPa pressure difference using a high-temperature and high-pressure fluid loss tester according to the provisions of 7.3 of GB / T16783.1.
[0064] (2) Evaluation of lubrication performance: 12 g of the copolymer prepared in each embodiment or comparative example was added to the base slurry at a high-speed stirrer speed of 11000 r / min and stirred for 20 min. After aging in a roller furnace at 180°C for 16 h, the base slurry was taken out and cooled to room temperature. The API filter loss was tested using an API filter loss meter to obtain a mud cake, and the viscosity coefficient of the mud cake was tested using a mud cake adhesion coefficient meter. The reduction rate of the mud cake viscosity coefficient was calculated according to formula (1).
[0065]
[0066] Where:
[0067] P 1 —Reduction rate of mud cake viscosity coefficient, %;
[0068] F v 0 —Viscosity coefficient of mud cake after aging at 180℃ / 16h;
[0069] F v —The viscosity coefficient of the mud cake after aging at 180℃ / 16h after adding the sample.
[0070] (3) Evaluation of viscosity increasing performance: 4 g of the copolymer prepared in each embodiment or comparative example was added to 400 mL of distilled water using a low-speed stirrer at a speed of 300 r / min. After stirring for 20 min, the reading at a speed of 600 r / min was measured using a six-speed rotary viscometer. The apparent viscosity was calculated according to formula (2).
[0071]
[0072] Where:
[0073] AV—apparent viscosity, mPa·s;
[0074] R 600 —Reading value of six-speed rotary viscometer at a speed of 600 r / min.
[0075] The base slurry formula used in the above tests is the same, and the formula is as follows:
[0076] 400 mL of distilled water was measured and placed in a cup, and 0.56 g of anhydrous sodium carbonate and 16 g of bentonite were added. A high-speed stirrer was used and set to a speed of 11000 r / min and stirred for 20 min. The mixture was stopped at least twice to scrape off the bentonite adhering to the container wall. After curing at 25°C for 24 h, 120 g of sodium chloride was added and stirred for 20 min at a speed of 11000 r / min to obtain a base slurry.
[0077] It should be noted that the amount of the temperature-resistant and salt-resistant copolymer with fluid loss reduction, viscosity increase and lubrication performance and other drilling fluid treatment agents provided by the present invention in the drilling fluid is calculated based on the amount of water used. For example, 400 mL (400 g) of distilled water is measured to prepare the base slurry, and 12 g of the temperature-resistant and salt-resistant copolymer with fluid loss reduction, viscosity increase and lubrication performance or other drilling fluid treatment agents is added, and the amount added is 3 parts by weight or 3%.
[0078] Example 1
[0079] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 2 g of corn starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0080] (2) While maintaining a stirring speed of 300 r / min, 10 g of phthalic anhydride, 4 g of sodium styrene sulfonate, 20 g of AMPS, and 1 g of acrylamide were added to solution A in sequence, the temperature was raised to 40° C., and stirred for 30 min to obtain a mixture B.
[0081] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 60°C, 0.5 g of ammonium persulfate was added dropwise to the mixture B, and the mixture was stirred for 2 min. The solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0082] Example 2
[0083] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 3 g of corn starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0084] (2) While maintaining a stirring speed of 300 r / min, 40 g of maleic anhydride, 8 g of sodium styrene sulfonate, 30 g of AMPS, and 6 g of N-hydroxymethyl acrylamide were added to solution A in sequence, the temperature was raised to 60° C., and stirred for 30 min to obtain a mixture B.
[0085] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 80°C, 1 g of potassium persulfate was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0086] Example 3
[0087] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 2 g of corn starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0088] (2) While maintaining a stirring speed of 300 r / min, 20 g of maleic anhydride, 10 g of sodium styrene sulfonate, 24 g of AMPS, and 3 g of acrylamide were added to solution A in sequence, the temperature was raised to 40° C., and stirred for 30 min to obtain a mixture B.
[0089] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 80°C, 0.5 g of ammonium persulfate was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0090] Example 4
[0091] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 3 g of corn starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0092] (2) While maintaining a stirring speed of 300 r / min, 30 g of maleic anhydride, 8 g of sodium allyl sulfonate, 26 g of AMPS, and 4 g of acrylamide were added to solution A in sequence, the temperature was raised to 60° C., and stirred for 30 min to obtain a mixture B.
[0093] (3) The stirring speed was maintained at 300 r / min and the temperature was kept constant at 60° C. 1 g of ammonium persulfate was added dropwise to the mixture B and stirred for 2 min. The solution was poured into a tray and dried at 105° C. for 24 h. The mixture was crushed and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0094] Example 5
[0095] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 2 g of sweet potato starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0096] (2) While maintaining a stirring speed of 300 r / min, 10 g of maleic anhydride, 8 g of sodium allyl sulfonate, 20 g of AMPS, and 1 g of N-hydroxymethyl acrylamide were added to solution A in sequence, the temperature was raised to 40° C., and stirred for 30 min to obtain a mixture B.
[0097] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 60°C, 0.5 g of potassium persulfate was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0098] Example 6
[0099] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 2 g of sweet potato starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0100] (2) While maintaining a stirring speed of 300 r / min, 40 g of phthalic anhydride, 10 g of sodium allyl sulfonate, 30 g of AMPS, and 6 g of acrylamide were added to solution A in sequence, the temperature was raised to 40° C., and stirred for 30 min to obtain a mixture B.
[0101] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 80°C, 1 g of potassium persulfate was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0102] Example 7
[0103] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 3 g of corn starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0104] (2) While maintaining a stirring speed of 300 r / min, 20 g of maleic anhydride, 9 g of sodium allyl sulfonate, 24 g of AMPS, and 3 g of N-hydroxymethyl acrylamide were added to solution A in sequence, the temperature was raised to 60° C., and stirred for 30 min to obtain a mixture B.
[0105] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 70°C, 0.5 g of initiator was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, sieved (sieve opening 0.59 mm), and a high-performance temperature-resistant and salt-resistant copolymer was obtained in the form of dry powder.
[0106] Example 8
[0107] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 3 g of sweet potato starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0108] (2) While maintaining a stirring speed of 300 r / min, 30 g of phthalic anhydride, 8 g of sodium allyl sulfonate, 25 g of AMPS, and 4 g of acrylamide were added to solution A in sequence, the temperature was raised to 60° C., and stirred for 30 min to obtain a mixture B.
[0109] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 70°C, 1 g of ammonium persulfate was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0110] Example 9
[0111] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 2 g of sweet potato starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0112] (2) Maintaining a stirring speed of 300 r / min, 20 g of maleic anhydride, 5 g of sodium allyl sulfonate, 20 g of AMPS, and 1 g of acrylamide were added to solution A in sequence, the temperature was raised to 40° C., and stirred for 30 min to obtain a mixture B.
[0113] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 60°C, 0.5 g of potassium persulfate was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0114] Example 10
[0115] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 2 g of sweet potato starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0116] (2) While maintaining a stirring speed of 300 r / min, 40 g of maleic anhydride, 10 g of sodium styrene sulfonate, 30 g of AMPS, and 6 g of acrylamide were added to solution A in sequence, the temperature was raised to 60° C., and stirred for 30 min to obtain a mixture B.
[0117] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 80°C, 1 g of ammonium persulfate was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0118] Embodiment 11
[0119] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 3 g of sweet potato starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0120] (2) While maintaining a stirring speed of 300 r / min, 40 g of maleic anhydride, 5 g of sodium styrene sulfonate, 24 g of AMPS, and 3 g of N-hydroxymethyl acrylamide were added to solution A in sequence, the temperature was raised to 60° C., and stirred for 30 min to obtain a mixture B.
[0121] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 70°C, 0.5 g of potassium persulfate was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0122] Example 12
[0123] (1) Keeping the stirring speed at 300 r / min, add 100 g of water and 3 g of corn starch into a four-necked flask equipped with a stirrer, a dropping funnel and a thermometer, and stir for 5 min to obtain solution A.
[0124] (2) While maintaining a stirring speed of 300 r / min, 30 g of maleic anhydride, 8 g of sodium styrene sulfonate, 26 g of AMPS, and 4 g of N-hydroxymethyl acrylamide were added to solution A in sequence, the temperature was raised to 40° C., and stirred for 30 min to obtain a mixture B.
[0125] (3) The stirring speed was maintained at 300 r / min, the temperature was raised to 70°C, 1 g of potassium persulfate was added dropwise to the mixture B, stirred for 2 min, the solution was poured into a tray, dried at 105°C for 24 h, crushed, and sieved (sieve opening 0.59 mm) to obtain a high-performance temperature-resistant and salt-resistant copolymer in the form of dry powder.
[0126] Comparative Example 1
[0127] The method for preparing the copolymer is similar to that of Example 8, except that 30 g of phthalic anhydride is not added to solution A in step (2).
[0128] Comparative Example 2
[0129] The method for preparing the copolymer is similar to that of Example 8, except that 8 g of sodium allyl sulfonate is not added to solution A in step (2).
[0130] Comparative Example 3
[0131] The method for preparing the copolymer is similar to that of Example 8, except that 25 g of AMPS is not added to solution A in step (2).
[0132] Comparative Example 4
[0133] The method for preparing the copolymer is similar to that of Example 8, except that 4 g of acrylamide is not added to solution A in step (2).
[0134] Performance Evaluation
[0135] (1) The high temperature and high pressure fluid loss, mud cake viscosity coefficient reduction rate and 1wt% aqueous solution apparent viscosity of the copolymers prepared in each embodiment and comparative example were tested, and the commercially available high performance fluid loss reducer DS-II (Shandong Deshunyuan Petroleum Technology Co., Ltd.) with temperature resistance of 180°C and salt resistance of 30% and the commercially available product RHPT-2 (Henan Longxiang Petroleum Additives Co., Ltd.) were selected as control samples. Both DS-II and RHPT-2 are one-dose drilling fluid treatment agents, and the addition amount thereof in each test is the same as that of the copolymers prepared in each embodiment and comparative example. The performance test results are shown in Table 1.
[0136] Table 1 Performance test results
[0137]
[0138]
[0139] It can be seen from the above performance test results that the copolymer provided by the present invention has excellent temperature and salt resistance, and can withstand temperatures of 180°C and 30% sodium chloride. In addition, the copolymer provided by the present invention has excellent fluid loss reduction, lubrication and viscosity increasing functions. In particular, the fluid loss reduction performance after high-temperature aging. After rolling aging at 180°C for 16 hours, the fluid loss reduction performance of the copolymers of each embodiment is less than 16mL, and can even be as low as 8-9mL, which meets the requirements of most domestic oil fields for fluid loss reduction performance against 180°C drilling fluid systems; at the same time, the copolymers of each embodiment improve the lubrication performance of the system by more than 68%, and have high viscosity increasing performance, which can meet the requirements of conventional polysulfone drilling fluid systems. As control samples, the two commercially available products DS-II and RHPT-2, although they can improve lubrication performance, their fluid loss reduction performance is significantly worse than that of the temperature-resistant and salt-resistant copolymers with fluid loss reduction, viscosity increasing and lubrication properties of the present invention.
[0140] (2) Through the performance evaluation experiment of the drilling fluid system, it can be concluded that in order to achieve the performance that is basically equivalent to that of the temperature-resistant and salt-resistant copolymer with fluid loss reduction, viscosity increase and lubrication performance provided in Example 8, it is necessary to form a drilling fluid system formula of "4% bentonite + 30% sodium chloride + 1% high-viscosity polyanionic cellulose + 4% sulfonated lignite + 4% sulfonated phenolic resin + 4% lignite resin + 2% lubricant". The drilling fluid system was aged at 180 degrees Celsius for 16 hours. The high-temperature and high-pressure fluid loss under the conditions of 180 degrees Celsius and 3.5 MPa pressure difference was 8.8 mL, and the reduction rate of the mud cake viscosity coefficient was 73.6%.
[0141] By comparison, it is found that when the amount of the temperature-resistant and salt-resistant copolymer with fluid loss reduction, viscosity increase and lubrication provided in Example 8 is 3 parts by weight, the improvement of the performance of the bentonite slurry containing salt water is basically the same as that of the above 5 drilling fluid treatment agents (1% high viscosity polyanionic cellulose + 4% sulfonated lignite + 4% sulfonated phenolic resin + 4% lignite resin + 2% lubricant) with an amount of 15 parts by weight. That is, when the temperature-resistant and salt-resistant copolymer with fluid loss reduction, viscosity increase and lubrication provided in Example 8 is added to the conventional drilling fluid system with a temperature resistance of 180°C, the addition of 4 drilling fluid treatment agents can be reduced from the perspective of the type of drilling fluid treatment agents, and the amount of drilling fluid treatment agents can be reduced by a total of 12 parts by weight while maintaining equivalent performance.
[0142] It can be seen from this that the temperature-resistant and salt-resistant copolymer with filtration loss reduction, viscosity increase and lubrication properties provided by the present invention can greatly reduce the types and amounts of treatment agents in the drilling fluid system, reflecting the high performance and multi-functionality of the product, greatly simplifying the formula of the high-temperature resistant drilling fluid system, and can effectively reduce the construction difficulty and construction work intensity.
[0143] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a temperature-resistant and salt-resistant copolymer having fluid loss reduction, viscosity increase and lubrication properties, characterized in that: include: The raw material components including natural polymer materials, organic acid anhydrides, vinyl-containing sulfonates, anionic monomers, crosslinking monomers and initiators are reacted in a solvent to obtain the temperature-resistant and salt-resistant copolymer with the performance of reducing fluid loss, increasing viscosity and lubricating.
2. The preparation method according to claim 1, characterized in that: The natural polymer material is a starch-based natural polymer material. Preferably, the natural polymer material includes at least one of corn starch and sweet potato starch; And / or, the organic acid anhydride comprises at least one selected from phthalic anhydride and maleic anhydride; and / or, the vinyl-containing sulfonate comprises at least one of sodium styrene sulfonate and sodium allyl sulfonate; and / or, the anionic monomer comprises 2-acrylamide-2-methylpropanesulfonic acid; and / or, the cross-linking monomer comprises at least one of acrylamide and N-hydroxymethyl acrylamide; and / or, the initiator comprises at least one of ammonium persulfate and potassium persulfate; And / or, the solvent comprises water.
3. The preparation method according to claim 1 or 2, characterized in that: The dosage of each component includes: Solvent: 100 parts by weight; Natural polymer material: 2-3 parts by weight; Organic acid anhydride: 10-40 parts by weight; Vinyl-containing sulfonate: 4 to 10 parts by weight; Anionic monomer: 20-30 parts by weight; Cross-linking monomer: 1 to 6 parts by weight; Initiator: 0.5-1 parts by weight; Preferably, The dosage of each component includes: Solvent: 100 parts by weight; Natural polymer material: 2-3 parts by weight; Organic acid anhydride: 20-30 parts by weight; Vinyl-containing sulfonate: 5 to 8 parts by weight; Anionic monomer: 24-26 parts by weight; Cross-linking monomer: 3-4 parts by weight; Initiator: 0.5-1 parts by weight.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The natural polymer material and the solvent are mixed and stirred; then the organic anhydride, the vinyl-containing sulfonate, the anionic monomer and the cross-linking monomer are added in sequence and stirred to dissolve; then the initiator is added and stirred to react at 60-80° C. to obtain the temperature-resistant and salt-resistant copolymer with the properties of reducing filtration loss, increasing viscosity and lubricating.
5. The preparation method according to claim 4, characterized in that: The stirring speed is 300-500 r / min; And / or, the stirring reaction time is 2 to 8 minutes.
6. The preparation method according to claim 4 or 5, characterized in that: The preparation method further comprises: drying, crushing and sieving the reaction product.
7. The preparation method according to claim 6, characterized in that: The drying temperature is 90-110° C., and the drying time is 16-30 hours.
8. A temperature-resistant and salt-resistant copolymer with fluid loss reduction, viscosity increase and lubrication properties, prepared by the preparation method described in any one of claims 1 to 7.
9. Use of the temperature-resistant and salt-resistant copolymer with fluid loss reduction, viscosity increase and lubrication properties as claimed in claim 8 in drilling fluid.
10. A drilling fluid, characterized in that: The drilling fluid comprises the temperature-resistant and salt-resistant copolymer with filtration reduction, viscosity increase and lubrication properties as described in claim 8.
Citation Information
Patent Citations
Preparation method of starch grafted copolymer inverse emulsion for drilling fluid
CN103113524A
Graft modified xanthan gum as well as preparation method and application thereof
CN111205396A
High-temperature-resistant organic silicon crosslinked starch filtrate reducer as well as preparation method and application thereof
CN115975112A
Deep-well polysulfonate drilling fluid and preparation method thereof
US9926482B1
Cited By
Polymer tackifier as well as preparation method and application thereof
CN121343060A
